Application of Mathematical Modelling to Factors Analysis Affecting Students’ Learningin Savannakhet University - PHONESAY , Latsamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this research was to analyze the factors that affect the learning of students in Savannakhet University. The sample group was the students who are studying in Savannakhet University from all faculties with a total number of 1,400 and the data analysis method was done though the SPSS program, MATLAB for windows and Microsoft Excel to calculate the frequency, percentages, standard deviation and the application of Mathematical Modelling (Analytical Hierarchy Process) for data analysis by calculating the matrix, eigenvalue and eigenvector that meets the largest eigenvalue of the collected data. The research results are as follows: 1) The teacher's factor has the most effect on the students' learning, covering the value of the impact level that affects the learning 0.3221, which means that the teacher's understanding of the subject taught and preparation of the lesson is not as good as it should be; 2) The student's behavior factors, which has the weight of the opinion that affects the learning equal to 0.2634 and the factor that affects the least learning, which covers the impact level value that affects the learning, which is equal to 0.0883 is the curriculum and instruction and from the result of the calculation, the value of CR=0.01042 shows that the information brought to the calculation is consistent and reliable. The main factor that affects the students' learning the most is the teacher (the quality of the teacher) with an impact value of 0.32206, followed by the student's behavior with an impact value of 0.26343 The third factor is the family with an impact value of 0.17466, while the fourth factor is the student's motivation with an impact value of 0.15156 and the last factor is the curriculum and instruction that has an effect level value of 0.08828.